2015
DOI: 10.1177/0333102415588328
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric differences suggest involvement of cerebellum and brainstem in chronic migraine

Abstract: CM patients showed significant volume differences in infratentorial areas and white-matter abnormalities in the posterior part of the brain. It is currently unclear whether the structural brain changes seen in migraine patients are the cause or the result of headaches. Longitudinal volumetric neuroimaging studies with larger groups, especially on the chronification of migraine, are needed to shed light on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 59 publications
7
53
0
Order By: Relevance
“…Bilgic et al (2016) found smaller brainstem volumes in migraine patients relative to healthy controls but no correlation between brainstem volume and clinical variables, such as disease duration and MIDAS scores. Positron emission tomography (PET) imaging of migraine patients during migraine attacks have found stronger functional activation in the periaqueductal gray (Weiller et al, 1995) stronger activation in the dorsolateral pons (Afridi et al, 2005) and stronger functional activation in midbrain regions (Weiller et al, 1995).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Bilgic et al (2016) found smaller brainstem volumes in migraine patients relative to healthy controls but no correlation between brainstem volume and clinical variables, such as disease duration and MIDAS scores. Positron emission tomography (PET) imaging of migraine patients during migraine attacks have found stronger functional activation in the periaqueductal gray (Weiller et al, 1995) stronger activation in the dorsolateral pons (Afridi et al, 2005) and stronger functional activation in midbrain regions (Weiller et al, 1995).…”
Section: Discussionmentioning
confidence: 62%
“…In a recent volumetric study, Bilgic et al demonstrated less brainstem volume in chronic migraine patients relative to healthy control subjects (Bilgic et al, 2016). Similarly, results by Jin et al demonstrate less cerebellar and brainstem density in migraine patients without aura relative to healthy controls using voxel-based morphometry (Jin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, sustained prolongation of STD in CM may arise from unremitting cellular injury in the brainstem and basal ganglia, in relation to frequent migraine attacks. In support of latter notion, impaired functional connectivity among, PAG, thalamus, cerebellum, insula, and other cortical areas as well as volumetric alterations including cortex, PAG, brainstem, and cerebellum were shown in migraine …”
Section: Discussionmentioning
confidence: 55%
“…In support of latter notion, impaired functional connectivity among, PAG, thalamus, cerebellum, insula, and other cortical areas as well as volumetric alterations including cortex, PAG, brainstem, and cerebellum were shown in migraine. 25,26 The processing of STD activates various brain structures including the ones already implicated in migraine pathophysiology such as sensorimotor cortex, insula, basal ganglia, substantia nigra, thalamus, and cerebellum. 20 Therefore, the STD test has an advantage to screen all of the above structures and may reveal temporary or persistent dysfunction in EM or CM respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that a decreased volume of cerebellum correlate with increased migraine duration, and this decreased cerebellum volume was statistically significant at longer than five years migraine patients. Bilgiç et al (2015) reported a significant reduction in the infratentorial region and the volume of cerebellum with migraine patients, but it is not known whether there were structural changes [11]. This relationship between a migraine and decrease cerebellum volume leads to cognitive and motor function loss over time.…”
Section: Discussionmentioning
confidence: 99%